ClustalW-MPI: ClustalW analysis using distributed and parallel computing - Li, Kuo-Bin (Bioinformatics, 2003)
ClustalW is a tool for aligning multiple protein or nucleotide sequences. The alignment is achieved via three steps: pairwise alignment, guide-tree generation and progressive alignment. ClustalW-MPI is a distributed and parallel implementation of ClustalW. All three steps have been parallelized to reduce the execution time. The software uses a message-passing library called MPI (Message Passing Interface) and runs on distributed workstation clusters as well as on traditional parallel computers. Availability:The source codes are written in ISO C and are available at http://www.bii.a-star.edu.sg/software/clustalw-mpi/. An open source implementations of MPI http://www-unix.mcs.anl.gov/mpi/. Contact: kuobin@bii.a-star.edu.sg